1997
DOI: 10.1152/ajpregu.1997.273.2.r833
|View full text |Cite
|
Sign up to set email alerts
|

Two types of leptin-responsive gastric vagal afferent terminals: an in vitro single-unit study in rats

Abstract: In vitro gastric vagal afferents' (GVAs) unit activities were recorded from the ventral GVA nerve strands in rats. The responsiveness of 16 GVA terminals to close intra-arterial injection of vehicle (0.1 ml), leptin (350 pmol), and cholecystokinin (CCK)-8 (10 pmol) was analyzed to generate a spike count-versus-time histogram. Data of 5-min spike counts before and after each treatment were normalized by dividing the latter by the former. A quotient (Q) > 1 indicates an excitatory effect, Q < 1 indicates an inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
105
1
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(114 citation statements)
references
References 0 publications
7
105
1
1
Order By: Relevance
“…These observations are consistent with leptin plus CCK interaction involving activation of CCK-A receptors located in visceral capsaicin-sensitive afferents, most likely of vagal origin. This is further supported by recent electrophysiological recordings in an isolated vagusstomach preparation in rats showing an increased responsiveness of gastric vagal afferents to leptin by pretreatment with CCK (27).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…These observations are consistent with leptin plus CCK interaction involving activation of CCK-A receptors located in visceral capsaicin-sensitive afferents, most likely of vagal origin. This is further supported by recent electrophysiological recordings in an isolated vagusstomach preparation in rats showing an increased responsiveness of gastric vagal afferents to leptin by pretreatment with CCK (27).…”
Section: Discussionsupporting
confidence: 67%
“…There is also evidence of synergistic interaction between peripheral CCK and other hormones released postprandially such as insulin and glucagon in rats (25,26). Recently, we observed in an in vitro vagus-stomach preparation that CCK increases responsiveness of vagal afferents to leptin as assessed electrophysiologically (27). Therefore, in the present study we investigate the potential functional synergistic interaction between peripheral leptin and CCK in the short-term modulation of food intake in lean mice.…”
mentioning
confidence: 91%
“…This satiation effect of leptin is synergistically enhanced by the presence of CCK (19). Extracellular single-unit recordings indicate that exogenous leptin alters the firing rate of vagal afferent fibers and that at least some of leptin-activated fibers are also activated by CCK (35). Finally, using cultured nodose ganglion neurons, we demonstrated that leptin rapidly increases cytosolic calcium in vagal afferents (18).…”
mentioning
confidence: 70%
“…Previous investigations using extracellular recording in vivo revealed that both leptin (35) and CCK (22) acutely activate Representative examples of membrane potential in cultured nodose neurons after bath application of leptin. The bars over the traces indicate the period of ligand application.…”
Section: Discussionmentioning
confidence: 99%
“…Leptin is produced in the mucosa of the stomach and rapidly mobilized by feeding and high doses of exogenous cholecystokinin (Bado et al, 1998), and it appears to activate vagal afferents (Wang et al, 1997), shown to express the long form of leptin receptor (Buyse et al, 2001;Burdyga et al, 2002). Small doses of leptin infused into the celiac artery significantly decreased sucrose intake and this effect was not observed in rats with subdiaphragmatic vagotomy or perivagal capsaicin-treatment aimed to selectively ablate vagal afferent fibers.…”
Section: Stomach: Stretch Tension Leptin and Ghrelinmentioning
confidence: 99%